Travel Medicine Encounters of Australian General Practice Trainees—A Cross‐Sectional Study. Issue 6 (2nd June 2015) - Morgan, Simon; Henderson, Kim M.; Tapley, Amanda; Scott, John; van Driel, Mieke L.; Spike, Neil A.; McArthur, Lawrie A.; Davey, Andrew R.; Catzikiris, Nigel F.; Magin, Parker J.
Abstract : Background: Travel medicine is a common and challenging area of clinical practice and practitioners need up‐to‐date knowledge and experience in a range of areas. Australian general practitioners (GPs) play a significant role in the delivery of travel medicine advice. We aimed to describe the rate and nature of travel medicine consultations, including both the clinical and educational aspects of the consultations. Methods: A cross‐sectional analysis from an ongoing cohort study of GP trainees' clinical consultations was performed. Trainees contemporaneously recorded demographic, clinical, and educational details of consecutive patient consultations. Proportions of all problems/diagnoses managed in these consultations that were coded "travel‐related" and "travel advice" were both calculated with 95% confidence intervals (CIs). Associations of a problem/diagnosis being "travel‐related" or "travel advice" were tested using simple logistic regression within the generalized estimating equations (GEE) framework. Results: A total of 856 trainees contributed data on 169, 307 problems from 108, 759 consultations (2010–2014). Travel‐related and travel advice problems were managed at a rate of 1.1 and 0.5 problems per 100 encounters, respectively. Significant positive associations of travel‐related problems were younger trainee and patient age; new patient to the trainee and practice; privately billing, larger, urban, and higher socioeconomic status practices; and involvement of the practice nurse. Trainees sought in‐consultation information and generated learning goals in 34.7 and 20.8% of travel advice problems, respectively, significantly more than in non‐travel advice problems. Significant positive associations of travel advice problems were seeking in‐consultation information, generation of learning goals, longer consultation duration, and more problems managed. Conclusions: Our findings reinforce the importance of focused training in travel medicine for GP trainees and adequate exposure to patients in the practice setting. In addition, our findings have implications more broadly for the delivery of travel medicine in general practice.